2018
DOI: 10.1136/neurintsurg-2018-014061
|View full text |Cite
|
Sign up to set email alerts
|

Stent retrievers with segmented design improve the efficacy of thrombectomy in tortuous vessels

Abstract: ESCAPE NCT01778335;SWIFT PRIME > NCT01657461; REVASCAT > NCT01692379; All post-results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 28 publications
(10 reference statements)
0
39
0
Order By: Relevance
“…Nevertheless, the study adds additional information to the current knowledge of MTB and could serve as a basis for the development of diagnostic tools in the future, thus enabling the operators to evaluate the AOI using preprocedural imaging in order to select the most adequate MTB technique. Furthermore, prediction of the location of the clot could allow the selection of the most effective thrombectomy device and the optimal interaction between the clot and the device used for MTB, improving the rate of first pass recanalization irrespective of the thrombectomy technique used 29–31…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the study adds additional information to the current knowledge of MTB and could serve as a basis for the development of diagnostic tools in the future, thus enabling the operators to evaluate the AOI using preprocedural imaging in order to select the most adequate MTB technique. Furthermore, prediction of the location of the clot could allow the selection of the most effective thrombectomy device and the optimal interaction between the clot and the device used for MTB, improving the rate of first pass recanalization irrespective of the thrombectomy technique used 29–31…”
Section: Discussionmentioning
confidence: 99%
“…They reported that the segments of an Embotrap (Cerenovus, Galway, Ireland) and Versi Retriever (NeuroVasc Technologies, Laguna Hills, CA, USA), which have a segmented design, remained even in a markedly flexed blood vessel, improving the recanalization rate. 17) In the present case, ADAPT was also performed to treat embolism of the cervical ICA, but the thrombus captured with an ACE60 came off at the site of DICA, making retrieval impossible. Mascitelli et al compared patients in whom ADAPT was successful with those in whom it was unsuccessful, and reported that factors for poor recanalization after ADAPT included a larger number of flexed blood vessels, larger vascular diameter, vascular diameter greater than that of a catheter, and a low clot burden score as an index for evaluating thrombus-occluded blood vessels.…”
Section: Disclosure Statementmentioning
confidence: 77%
“…Generally, vascular tortuosity highly influences prompt endovascular access and clot retrieval during MT. 7,8 For instance, ICA siphon and the V3 segment of the VA, which represent innate vessels at an acute angle, would increase the complexity of navigating and retrieving the device. Conversely, if the vascular angle and vessel calibre are appropriate anatomically, MT can be possible even in a collateral pathway.…”
Section: Discussionmentioning
confidence: 99%